Awareness Regarding Osteoporosis among Menopausal Women in Tanahu - Acharya, Shusma; Mandal, Reena; Thapa, Karuna (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Osteoporosis is the one of the global health problems of the world including Nepal and it has become a major public health issue. Females are eight times more at risk for developing osteoporosis than males, especially the menopausal women. The objective of this study was to assess the level of awareness regarding osteoporosis among menopausal women in a community. Method: This was a descriptive cross sectional study which was conducted among 88 menopause women residing in Suklagandaki municipality, Tanahu. Non probability purposive sampling method was used and data was collected through face to face interview and analyzed. Chi-square test and Fischer exact test were used to measure the association between the levels of awareness with socio demographic variables using SPSS and the findings were considered significant if p <0.05. Findings were then presented in tabulated form. Results: Less than half (30.6%) of the respondents had an adequate level of awareness regardingosteoporosis. Respondents demonstrated better awareness on time for getting vitamin D (39.7%) as a preventive measure and facture of bone (31.8%) as a complication of osteoporosis. A significant association was found between awareness level and education (p < 0.01), occupation (p < 0.01), religion (p < 0.04), and monthly income (p < 0.001) in this study. Conclusion: Majority of respondents had inadequate awareness about osteoporosis. Targeted awareness and educational programs are recommended to enhance knowledge and promote preventive practices among menopausal women.